Pengaruh Bukaan Pada Kubah Terhadap Pencahayaan Alami : (Studi Kasus: Masjid Al Huda, Embong Arab Malang) - Archsiddiqie Aliya, Lissania; Jono Wardoyo, ST., MT (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2024)
The natural lighting produced in buildings in densely populated settlements make it very difficult to get natural lighting from the side, so the dome becomes one of the important central points for the entry of light in the building. The case study was found at the Al Huda Mosque, Embong Arab Malang which has openings in the dome with a type of colored glass material, totaling 24 openings. The existence of this study is to determine the effet of openings in the mosque dome on the intensity of natural lighting in the interior space. The method applied is quantitative with details, field measurements using lux meters and experimental simulations using DIALux Evo 11.1 software. The results of this study state that the presence of openings greatly affects the light in the building. If do not apply openings to the dome, it will cause less that optimal light performance and if apply openings with a transparent type of glass material, it will produce a high value of natural lighting intensity but it is possible to produce glare.